Pembelajaran Abad-21 Melalui Model Project Based Learning Terintegrasi STEM (PJBL-STEM) dalam Meningkatkan Kemampuan Berpikir Tingkat Tinggi - Effendi, Muhammad Idris; Yoto, Yoto (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to explore and describe the application of Project Based Learning which is integrated with the STEM (Science, Technology, Engineering, Mathematics) approach in improving the high-level thinking abilities of Automotive Engineering Education students. The research method used is a qualitative approach with a descriptive approach. Data was collected through literature studies which included printed books, scientific journals, and articles related to project-based learning and STEM approaches. The conclusion from the literature study shows that the application of the PjBL-STEM Learning Model is effective in developing students' higher order thinking skills. PjBL provides encouragement for active student involvement, increases interest and motivation to learn, and produces meaningful learning. In addition, the STEM approach trains students to apply knowledge in solving environmental problems by utilizing technology. The profile of Automotive Engineering Education graduates in the 21st century is designed to prepare individuals as leaders in various automotive-related fields, with high-level thinking abilities as a strong foundation in facing the challenges of the modern automotive industry. The results of this research confirm that the development of high-level thinking abilities is a key element in automotive engineering education in the current era.